Repairing the rubble of the river bank / Muhammad Nur Ikhwan Mohamad Hanafiah - Mohamad Hanafiah, Muhammad Nur Ikhwan (Universiti Teknologi MARA, Perak, 2021)
Objective of this research is to know the construction method of Repairing the rubble of riverbank at Jalan Pohon Celagi, Pasir Mas, Kelantan. Besides, can learn more knowledge about study the factors that required in construction. I also be able to identify the material used in construction and identify the machineries that used in this project construction. This contract period of this project is 9 months which start at August 2021 and will be complete in May 2022. The contract value of this project is RM .Method of the study that perform in this project is observation and interview.